Virion Structure of Iflavirus Slow Bee Paralysis Virus at 2.6-Angstrom Resolution - Kalynych, Sergei; Přidal, Antonín; Pálková, Lenka; Levdansky, Yevgen; de Miranda, Joachim R; Plevka, Pavel (Journal of virology, 2016)
UNLABELLED: The western honeybee (Apis mellifera) is the most important commercial insect pollinator. However, bees are under pressure from habitat loss, environmental stress, and pathogens, including viruses that can cause lethal epidemics. Slow bee paralysis virus (SBPV) belongs to the Iflaviridae family of nonenveloped single-stranded RNA viruses. Here we present the structure of the SBPV virion determined from two crystal forms to resolutions of 3.4 Å and 2.6 Å. The overall structure of the virion resembles that of picornaviruses, with the three major capsid proteins VP1 to 3 organized into a pseudo-T3 icosahedral capsid. However, the SBPV capsid protein VP3 contains a C-terminal globular domain that has not been observed in other viruses from the order Picornavirales The protruding (P) domains form "crowns" on the virion surface around each 5-fold axis in one of the crystal forms. However, the P domains are shifted 36 Å toward the 3-fold axis in the other crystal form. Furthermore, the P domain contains the Ser-His-Asp triad within a surface patch of eight conserved residues that constitutes a putative catalytic or receptor-binding site. The movements of the domain might be required for efficient substrate cleavage or receptor binding during virus cell entry. In addition, capsid protein VP2 contains an RGD sequence that is exposed on the virion surface, indicating that integrins might be cellular receptors of SBPV. IMPORTANCE: Pollination by honeybees is needed to sustain agricultural productivity as well as the biodiversity of wild flora. However, honeybee populations in Europe and North America have been declining since the 1950s. Honeybee viruses from the Iflaviridae family are among the major causes of honeybee colony mortality. We determined the virion structure of an Iflavirus, slow bee paralysis virus (SBPV). SBPV exhibits unique structural features not observed in other picorna-like viruses. The SBPV capsid protein VP3 has a large C-terminal domain, five of which form highly prominent protruding "crowns" on the virion surface. However, the domains can change their positions depending on the conditions of the environment. The domain includes a putative catalytic or receptor binding site that might be important for SBPV cell entry.
Keywords: virion; molekulární modely; Crystallography, X-Ray; Viral Structures; Models, Molecular; RNA-viry; krystalografie rentgenová; RNA Viruses; Animals; Virion; virové struktury; kapsida; Capsid; zvířata; včely; Bees